Societal impact for patients with psoriasis: A nationwide Swedish register studyCapsule Summary - Henrike Häbel, PhD; Björn Wettermark, PhD; David Hägg, PhD; Reginald Villacorta, PhD; E.Christina M. Wennerström, PhD; Marie Linder, PhD (Elsevier, 2021)
Background: Psoriasis is an immune-mediated chronic inflammatory disease having a significant negative health impact. Psoriasis has societal impact; loss of productivity has been estimated at approximately 10% and it may influence the patient's financial status. Relationships between quality of life, disease severity, and cost of care need exploration. Understanding the disease burden is important for health policy and research allocation. Few studies address the research gaps in socioeconomics, comorbidity, and medication use. Objective: Observing differences in education, income, employment status, marital status, health care consumption, and drug utilization between patients with psoriasis and matched controls. Methods: Cohort study following socioeconomics and health care consumption for all psoriasis patients from the Swedish patient register. All individuals with a first diagnosis of psoriasis in outpatient or inpatient care from 2002 to 2013 were followed until death, emigration, or end of the study. Results: Overall, 109,803 patients were included (mean age 51.2 years, 53% women) and matched with 1.08 million controls. The levels of education and income were similar, but the proportion employed was significantly lower for patients with psoriasis. There was a tendency for fewer patients with psoriasis to be married. Limitations: Generalizability, lack of primary care diagnoses, and lack of early treatments (available from 2005). Conclusion: Understanding of the socioeconomic impact of psoriasis is extended by showing reductions in employment.